Pain and substance-related pain-reduction behaviors among opioid dependent individuals seeking methadone maintenance treatment. - Barry, Declan T; Beitel, Mark; Joshi, Dipa; Schottenfeld, Richard S (The American journal on addictions / American Academy of Psychiatrists in Alcoholism and Addictions, 2009)
We surveyed 293 opioid dependent individuals seeking methadone maintenance treatment about their pain experiences and their substance-related pain reduction behaviors. Among the 213 respondents reporting recent pain of at least moderate typical pain intensity, two-thirds had a lifetime history of chronic pain. In comparison to those without a lifetime history of chronic pain, those with a lifetime history were older, reported higher pain frequency, were more likely to endorse accident or surgery and less likely to endorse "don't know" as the genesis of their recent pain, and endorsed comparable levels of substance-related pain reduction behaviors. These findings may have implications for resource and program planning in MMT programs.
Keywords: Adult; Analgesia; Chronic Disease; Female; Humans; Male; Methadone; Opioid-Related Disorders; Pain; Patient Acceptance of Health Care; Substance Abuse Treatment Centers